PEMBINAAN PEMANDU WISATA BERBAHASA INGGRIS, PENGAJARAN TARI DAN TATA RIAS BALI DALAM UPAYA MENDUKUNG DESA KERAMBITAN SEBAGAI DESA WISATA DI KABUPATEN TABANAN - Yulianti, Ni Ketut Dewi (FKIP Universitas Wisnuwardhana, 2023)
The purpose of this PKM activity is to promote Kerambitan village by providing guidance to English-speaking tour guides, as well as providing solutions to the problems of Kerambitan village that requires Balinese dancers who are also also mastering Balinese makeup to support castle tourism and be able to introduce Kerambitan village as a tourist destination. The implementation method for PKM activities is divided into two, namely the training method and the field practice method as well as performing and recording. The outputs achieved in the implementation of this PKM are recordings and photographs of the process of English training and dance and make-up for the Pendet dance. PKM activities in Kerambitan village focus on training activities for English-speaking tour guides and training for the Pendet dance and make-up.